A Patient Presented as Gluteal Abscess Diagnosed to be a Case of Pott’s Spine with Psoas Abscess: A Case Report - Verma, Dr. Jyoti; Pankaj, Dr. Jyoti; Abbasi, Dr. Tabish (International Journal of Innovative Research in Medical Science, 2025)
A gluteal abscess can be a manifestation of Pott’s spine. The most common cause of gluteal abscess is parentral drug administration using contaminated needles. Other causes include infected hematoma, seroma, posttraumatic sepsis and spread of intrapelvic sepsis to the gluteal region. Here a case is presented where a middle-aged female patient was admitted for the complain of recurrent gluteal abscess for 1 year for which surgical drainage was done several times outside before coming to the present hospital. She developed complain of lower back since few months which was ignored by the patient herself. She had other complained of other constitutional symptoms. Later on investigation it was diagnosd to be a case of pott’s spine which has sinus track to gluteal muscle.